Symptom Distress as Predictors of Sexual Dissatisfaction among Nursing Mothers in Awka, Nigeria. - Nwosu, Harry Obi; Chinenye, Ifedigbo; Bentina, Mathias (Advances in Social Sciences Research Journal, 2015)
Sexual dissatisfaction may best be described as a multidimensional experience involving thoughts, feelings, personal and socio-cultural attitudes and beliefs, combined with biological factors. This also involves any situation in which one or more sexual partners is unhappy with the quality, style or quantity of sexual activity in which they are engaging. In this study, the researchers investigated symptom distress as predictors of sexual dissatisfaction among nursing mothers in Awka. A total number of 220 nursing mother volunteers from Awka North and South LGAs and participated in the study. The age of the participants ranged from 18 to 50, with a mean age of 27.69 years, and standard deviation of 5.17. The Symptom distress checklist- 90 (1977) and Index of sexual satisfaction (1982), with reliability co-efficient which ranged from .77 to .90 and .92, were used for data collection. The collected data was analyzed using multiple regression analysis. The result showed that: 1) Psychoticism followed by Paranoid Ideation, Depression, Somatization, Hostility and Obsessive-compulsive predicted Sexual Dissatisfaction negatively among nursing mothers in Awka. 2) Phobic anxiety followed by Interpersonal sensitivity, Anxiety and Neuroticism predicted sexual dissatisfaction positively in the same population. Based on the findings of the study, the researchers recommended that Doctors, Nurses, Family therapists, Counselors and Clergy should give more attention to the psychological needs of women at this time (post natal period) and indeed at all times so as to make couples and young families healthier.